If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9e + -7 = 65 Reorder the terms: -7 + 9e = 65 Solving -7 + 9e = 65 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 9e = 65 + 7 Combine like terms: -7 + 7 = 0 0 + 9e = 65 + 7 9e = 65 + 7 Combine like terms: 65 + 7 = 72 9e = 72 Divide each side by '9'. e = 8 Simplifying e = 8
| 9e-4=24.8 | | 19=6c-5 | | 1.6x+2.4=16.8 | | 17+16+x/2=20 | | 2.2=2y | | P-5=1 | | 14=4c-2 | | 6e-5=19 | | 6d+3=4d+21 | | (-4/25)-(4/9x) | | x+5/25 | | 25/x+5 | | x-5=51 | | ((x/25)-(1/x))/1+(5/x) | | 3+4+x=20 | | (3q-4)(2q+5)=0 | | 20k-15=18x-7 | | (x/25)-(1/x)/1+(5/x) | | 2x/(x^2-16)=3/(x^2-16)-1/(x-4) | | 4.75+4.75+5.50+4.75+3.75= | | (x+7)(x+3)=0 | | 15(x+4)= | | (3x-1)(3x-1)=5 | | (-5x+6)/2+(7/2)=(-4x/5) | | -8+x=-2 | | 9x^2+26x+20=0 | | 15(x/4)= | | 5(3-d)+2=2 | | 7(3-m)-11=-4 | | 11=-4+7e+9-e | | x-x=1-1 | | 15+3w+12+w=3 |